1987
DOI: 10.1093/oxfordjournals.humrep.a136607
|View full text |Cite
|
Sign up to set email alerts
|

Premature luteinization of follicles during ovarian stimulation for in-vitro fertilization

Abstract: The structure and growth of developing follicles was monitored using vaginal ultrasound scanning in an outpatient programme of in-vitro fertilization (IVF) and embryo transfer (ET). Patients received either human menopausal gonadotrophin (HMG) alone or clomiphene citrate (CC) + HMG for controlled ovarian stimulation. Ultrasound data were compared with pre-ovulatory oestradiol (E2), luteinizing hormone (LH) and progesterone (P) levels. Hormonal parameters and results were classified according to the main indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Vaginal ultrasound scanning seems to be helpful in the evaluation of minor changes in the follicular structure, correlating frequently with hormonal findings [16]. Ultrasonic features of PL of follicles are thickening of the follicular wall and the appearance of irregular echogenic structures in the follicle.…”
Section: Definitionmentioning
confidence: 99%
“…Vaginal ultrasound scanning seems to be helpful in the evaluation of minor changes in the follicular structure, correlating frequently with hormonal findings [16]. Ultrasonic features of PL of follicles are thickening of the follicular wall and the appearance of irregular echogenic structures in the follicle.…”
Section: Definitionmentioning
confidence: 99%
“…Premature serum P elevation on or before the day of hCG administration during controlled ovarian hyperstimulation (COH) and the concomitant differentiation of granulosa cells (GC) to luteal cells is usually called premature luteinization (PL) (1). Despite the introduction of GnRH analogue into clinical practice and the effective suppression of endogenous gonadotropins, the prevalence rate of premature luteinization in long GnRH agonist (GnRH-a) cycles has been reported from 13% (2) -61% (3).…”
mentioning
confidence: 99%
“…Since then, more or less aggressive forms of controlled ovarian stimulation (COH) have been described to increase the oocyte yield and the number of zygotes available for transfer. One initial complication of COH treatments was the presence of premature LH surges resulting in poor IVF outcome [5]. Multiple authors [6,7] have shown the benefits of GnRH-a use in preventing a premature LH surge in IVF.…”
Section: Discussionmentioning
confidence: 99%